2017
DOI: 10.1111/ppl.12636
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling reveals mechanisms of sexually dimorphic responses of Populus cathayana to potassium deficiency

Abstract: Potassium (K) deficiency causes a series of physiological and metabolic disorders in plants, and dioecious species exhibit different responses based on sex. Our previous morphological and physiological observations indicated that Populus cathayana males were more tolerant to K deficiency than females. To continue this work, comparative transcriptome analyses were carried out to investigate sexually differentially expressed genes (DEGs) in this study. The results indicate that 10 weeks of K deficiency result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…is an ecologically and economically important dioecious species, commonly cultivated in valley or mountain areas of China, where soil P availability is low. P. cathayana males and females have differences in stress tolerance and resource demands and they show different physiological and morphological responses to nutrient limitation, male poplars being more tolerant than females (Zhang et al 2014, Han et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…is an ecologically and economically important dioecious species, commonly cultivated in valley or mountain areas of China, where soil P availability is low. P. cathayana males and females have differences in stress tolerance and resource demands and they show different physiological and morphological responses to nutrient limitation, male poplars being more tolerant than females (Zhang et al 2014, Han et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Plants react to the low-K + levels by influencing root growth and structure in different ways, such as suppressing primary roots’ growth and promoting root hair elongation [ 3 ]. In plants, low-K + signal transduction causes a downstream response and ultimately promotes their adaptation to K + deficiency [ 4 ]. K + deficiency can activate K + uptake through the plant root by influencing the K + transporters’ activity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Populus cathayana Rehd. is a rapidly growing dioecious plant, and males are better than females under environmental stress such as drought and nutrient deficiency ( Chen et al, 2014 ; Han et al, 2018 ). Previous studies have demonstrated that males of P. cathayana adopt energy-saving strategies to cope with P deficiency by metabolic and physiological analysis, resulting in stronger tolerance to P deficiency than females ( Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%